Technology and equipment for harvest and transportation of grain in selection and primary seed breeding - N. E. Evtyushenkov; M. L. Kryukov; E. P. Shilova; S. V. Vlasova (Сельскохозяйственные машины и технологии, 2016)
Trial plots are necessary for breed new varieties and renewal of the used ones on a scientific basis. Efficiency and an intensification of selection breeding and seed production processes substantially depends on technique of selection establishments. Creation of new generation of machines should be carried out according to the reached technological level and constructive decisions directed on resource-saving and the fullest accounting of agrobiological features of objects of machine influence, especially grain crops. In the course of grain harvest and transportation when selection works the bags complicated mechanization of process of delivery of grain from the harvester to a point of processing was widely applied so far. The authors suggested to substitute soft bags for rigid containers. Dimensions of transportation containers should be not exceeding a cross internal dimension of vehicles or multiply to take place in this dimension. The container dimension in the plan is a square with side not less than 1120 mm and high not less than 565 mm. A bottom of containers for grain drying is holed, a grain layer is no more than 300 mm. Due to containers advantages technological capabilities are possible: transportations of grain from the harvest to the point of grain processing, grain drying in containers, a mechanized unloading. Use of such containers will allow to lower labor and farm costs and by 5 times, to double filling of warehouses, completely to liquidate manual works at loading and unloading operations, to reduce wasted time by 1.5-2 times.